Features Of Technical Training of Swimmers Using the Method of Circular Training and Special Exercises - Abdalimova R.M. (Zien Journals, 2022)
The work is dedicated to the technical training of swimmers. The paper reveals the features of the technical readiness of swimmers with the help of special exercises used by the circuit training method
Keywords: swimming; technical training; circuit training